A fuzzy approach to measuring violence against women and its severity - Francesca Bettio; Elisa Ticci; Gianni Betti (Global Labor Organization (GLO), 2018)
We develop a scale of severity of violence against women based on fuzzy set theory. The scale can be used to derive fuzzy indexes of violence which account for the prevalence, frequency and severity of violence. Using the results of the survey conducted by the European Agency for Human Rights (FRA) we find strong congruence of ranking between the proposed scale and three widely used alternatives – the Conflict Tactic Scale, The Severity of Violence Against Women Scale and the Index of Spouse Abuse. Unlike existing alternatives, however, the scale that we propose is based on objective information rather than subjective assessment; it is parsimonious in terms of the amount of information that it requires; and it is less vulnerable to risks of cultural bias. As an example of the uses to which fuzzy measurement of violence can be put, we compute fuzzy indexes of intimate partner violence for European countries and find a clear, inverse correlation across countries with the degree of gender equality.
Keywords: C49; D63; J16; 330; violence against women; fuzzy set theory; severity of violence scales; Europe; gender